Risk factors for syphilis in women: case-control study - Vilma Costa de Macêdo; Pedro Israel Cabral de Lira; Paulo Germano de Frias; Luciana Maria Delgado Romaguera; Silvana de Fátima Ferreira Caires; Ricardo Arraes de Alencar Ximenes (Revista de Saúde Pública, 2017)
ABSTRACT OBJECTIVE To determine the sociodemographic, behavioral, and health care factors related to the occurrence of syphilis in women treated at public maternity hospitals. METHODS This is a case-control study (239 cases and 322 controls) with women admitted to seven maternity hospitals in the municipality of Recife, Brazil, from July 2013 to July 2014. Eligible women were recruited after the result of the VDRL (Venereal Disease Research Laboratory) under any titration. The selection of cases and controls was based on the result of the serology for syphilis using ELISA (enzyme-linked immunosorbent assay). The independent variables were grouped into: sociodemographic, behavioral, clinical and obstetric history, and health care in prenatal care and maternity hospital. Information was obtained by interview, during hospitalization, with the application of a questionnaire. Odds ratios and 95% confidence intervals were estimated using logistic regression to identify the predicting factors of the variable to be explained. RESULTS The logistic regression analysis identified as determinant factors for gestational syphilis: education level of incomplete basic education or illiterate (OR = 2.02), lack of access to telephone (OR = 2.4), catholic religion (OR = 1.70 ), four or more pregnancies (OR = 2.2), three or more sexual partners in the last year (OR = 3.1), use of illicit drugs before the age of 18 (OR = 3.0), and use of illicit drugs by the current partner (OR = 1.7). Only one to three prenatal appointments (OR = 3.5) and a previous history of sexually transmitted infection (OR = 9.7) were also identified as determinant factors. CONCLUSIONS Sociodemographic, behavioral, and health care factors are associated with the occurrence of syphilis in women and should be taken into account in the elaboration of universal strategies aimed at the prevention and control of syphilis, but with a focus on situations of greater vulnerability.